ISLAMIC RELIGIOUS EDUCATION IN SHAPING CHARACTER IN HIGHER EDUCATION: Indonesia - Nurlela; Evi Gusliana; Dwi Rohmadi Mustofa (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
AbstractCharacter formation is associated with the term ethics, morality, and or values related to moral strength, connoting "positive" and "good" not neutral. Therefore, character education more broadly can be interpreted as education that develops cultural values and national character in students so that they have values and character as their own character, apply these values in their lives as members of society, and religious citizens. nationalist, productive, and creative. The application of Islamic education needs to be done by increasing taqwa to God Almighty and noble character is a manifestation of the faith that is believed by everyone. Therefore, faith and piety that are united in a person will shape a person into a good, strong, honest and responsible person. With a strong character, it will be very useful for the unity and future of the nation. Character education in higher education is very important because it creates a young generation that is honest, polite and ethical. [1]Keywords: Islamic religious education, character, higher education